2010
DOI: 10.1016/j.febslet.2010.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Sequence discrimination of the Zα domain of human ADAR1 during B–Z transition of DNA duplexes

Abstract: Edited by Gianni Cesareni

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Recently, NMR studies of complexes between hZa ADAR1 and non-CG-repeat DNA duplexes have shown that the k ex values for the B-form imino protons of the d(CACGTG) 2 and d(CGTACG) 2 are significantly altered by complex formation with hZa ADAR1 (Fig. 4B) [22]. This result strongly suggests that the BP complex also exists as intermediate structure during the B-Z transition of DNA duplexes that is induced by hZa ADAR1 .…”
Section: Discussionmentioning
confidence: 83%
“…Recently, NMR studies of complexes between hZa ADAR1 and non-CG-repeat DNA duplexes have shown that the k ex values for the B-form imino protons of the d(CACGTG) 2 and d(CGTACG) 2 are significantly altered by complex formation with hZa ADAR1 (Fig. 4B) [22]. This result strongly suggests that the BP complex also exists as intermediate structure during the B-Z transition of DNA duplexes that is induced by hZa ADAR1 .…”
Section: Discussionmentioning
confidence: 83%
“…The sequences were the substitute for d(CG) 6 and often used for discussion on the manner of interaction between Za and Z-DNA [31,32]. The sequence (CACGTG) 2 , (CGTACG) 2 , or (CGGCCG) 2 can co-crystallize with human Za ADAR1 , respectively [31], so Ha et al [31] considered hZa ADAR1 recognized Z-DNA in a conformation-specific manner, but not in a sequencespecific manner.…”
Section: Discussionmentioning
confidence: 99%
“…The non-(GC) repeat sequences were more difficult to form Z-DNA than d(CG) repeat sequences. Because non-(GC) repeat sequences had very low-binding affinity for Za ADAR1 than alternating d(CG) DNA, Seo et al [32] considered the possibility of flipping B-DNA into Z-DNA for non-(GC) repeat sequences was far below than alternating d(CG) DNA duplex.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent relaxation rate constant of water (R 1w ) was determined by selective inversion recovery experiment using a DANTE sequence for selective water inversion. [12][13][14] The hydrogen exchange rate constants of the imino protons (k ex ) were measured by a water magnetization transfer, where a selective 180 o pulse for water was applied, followed by a variable delay, and then a 3-9-19 acquisition pulse was used to suppress the water signal. 12 The intensities of each imino proton were measured with 20 different delay times ranging from 5 to 100 ms.…”
Section: Experimental Methodsmentioning
confidence: 99%